Urban green management plan: Guidelines for European cities - Battisti, Luca; Larcher, Federica; Devecchi, Marco (Frontiers in Horticulture, 2023)
Urban green areas are essential components of a city. They guarantee an adequate quality of life by providing several ecosystem services. Green areas must be designed and managed appropriately with a long-term approach ensuring a healthy urban ecosystem. It is possible to observe how especially in the USA and Canada there is a useful tool for this purpose, the Urban Forest Management Plan. The aim of this study is to understand which practical and effective plans were available for manage public urban green spaces in Europe, before COVID-19 (non-routine period), in order to carefully set up management plans. In order to reach the goal, a bibliographic review was performed and reported following the PRISMA Statement. Furthermore, a research was carried out on the main management plans adopted by the municipalities in European capitals. In this regard, the research tries to investigate the knowledge base that European municipalities can use to set up an urban green management plan. The narration of the outcomes was designed as an initial guide aimed primarily at public administrators by providing them with a path and a scheme on how to structure a long-term green management plan in European cities. In the hope that even European municipalities can adopt a long-term green management plan, we propose a scheme to be followed to achieve this goal, with the indication of five essential points to be taken into account.